Neighborhood safety and physical inactivity in adults from Curitiba, Brazil - Rech, Cassiano Ricardo (BioMed Central, 2012)
BACKGROUND: Neighborhood safety is one of the environmental aspects that can influence physical activity. We analyzed the association between perceived neighborhood safety and physical inactivity (PI) in adults and examined effect modification according to sociodemographic variables. METHODS: A cross-sectional study was conducted with 1,261 adults (62% women), age 18–69 years from Curitiba, Brazil. RESULTS: The perception of unsafe neighborhood was higher among women, older participants, those classified in the high socioeconomic (SES) group, overweighed and also among those reporting to have PA equipments and children. The association between perception safety of walking during the day and walking for leisure (women PR = 1.12 CI(95%) = 1.02–1.22; men PR = 0.82 CI(95%) = 0.64–1.05; interaction term PR = 1.38 CI(95%) = 1.03–1.83) and safe perception was associated with PI, just in the highest SES group (PR = 1.09; CI(95%) = 1.00–1.19; p trend = 0.032) when compared with their counterparts (low SES PR = 0.99; CI(95%) = 0.90–1.04; p trend = 0.785; interaction term PR = 1.09; CI(95%) = 1.03–1.15; p trend = 0.007). CONCLUSION: The perception of safety in the neighborhood was associated with PI in transport, but this association varies across of sociodemographic variables.